Att mäta forskning — naturvetenskapen som norm - Myrdal, Janken (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
This article discusses the difference between the natural sciences and the human sciences (humanities and social sciences) as different crafts of science, and especially in relation to different forms of publication. In the natural sciences, publication of research results in articles totally dominate, while in the human sciences, extensive monographs are often the most estimated form of publication. With a changed culture of evaluation, articles published in journals registered in ISI have been given a paramount importance. This simplified form of evaluation will alter researchers' publication habits, and natural scientists will be the first to answer to the focus on ISI journals. Human sciences run a risk that the thorough and critical analysis of human behavior will be disadvantaged. Statistics show that the performance of human sciences is underestimated with the prevalent measures, and the article proposes the building of a database for scholarly books, and the avoidance of simplified measures for research output.